MODELING OF HEAT TRANSFER PHENOMENA IN THE PROCESS OF COAL PYROLYSIS - Siswanto, Kindriari Nurma Wahyusi; Utami, Lucky Indrati (Acta Scientiae et Intellectus, 2024)
A steady state model of heat transfer phenomena coal pyrolisis in a batch reactor has been developed. The reactor was heated from the outside. The study was focussed on the heat transfer process in connection with the product distribution, especially on the tar product. Nusselt number had been choosen as the control number in the heat transfer process. From this study it is found that the highest tar product happened when the process temperature was 600 0C, the particle size was 6/8 mesh, and Nusselt Number was 253.887.